Experimental Study of the Heat-Transfer Performance of an Extra-Long Gravity-Assisted Heat Pipe Aiming at Geothermal Heat Exploitation - Jiwen Cen (MDPI AG, 2021)
The installation and operation of enhanced geothermal systems (EGS) involves many challenges. These challenges include the high cost and high risk associated with the investment capital, potential large working-fluid leakage, corrosion of equipment, and subsiding land. A super-long heat pipe can be used for geothermal exploitation to avoid these problems. In this paper, a high aspect-ratio heat pipe (30 m long, 17 mm in inner diameter) is installed vertically. Experiments are then carried out to study its heat-transfer performance and characteristics using several filling ratios of deionized water, different heating powers, and various cooling-water flowrates. The results show that the optimal filling-ratio is about 40% of the volume of the vaporizing section of the heat pipe. Compared with a conventional short heat pipe, the extra-long heat pipe experiences significant thermal vibration. The oscillation frequency depends on the heating power and working-fluid filling ratio. With increasing cooling-water flow rate, the heat-transfer rate of the heat pipe increases before it reaches a plateau. In addition, we investigate the heat-transfer performance of the heat pipe for an extreme working-fluid filling ratio; the results indicate that the lower part of the heat pipe is filled with vapor, which reduces the heat-transfer to the top part. Based on the experimental data, guidelines for designing a heat pipe that can be really used for the exploitation of earth-deep geothermal energy are analyzed.